Nutrient Requirements and Basics of Nutritional Status Assessment Malnutrition Problems - Sehfiani, Indah (Jurusan Pendidikan Islam Anak Usia Dini, 2024)
This article examines the critical importance of nutrition for children from birth to six years of age, a period identified as the